Nitride Spinel: An Ultraincompressible High‐Pressure Form of BeP2N4. (7th November 2019) - Vogel, Sebastian; Bykov, Maxim; Bykova, Elena; Wendl, Sebastian; Kloß, Simon D.; Pakhomova, Anna; Dubrovinskaia, Natalia; Dubrovinsky, Leonid; Schnick, Wolfgang
Abstract: Owing to its outstanding elastic properties, the nitride spinel γ‐Si3 N4 is of considered interest for materials scientists and chemists. DFT calculations suggest that Si3 N4 ‐analog beryllium phosphorus nitride BeP2 N4 adopts the spinel structure at elevated pressures as well and shows outstanding elastic properties. Herein, we investigate phenakite‐type BeP2 N4 by single‐crystal synchrotron X‐ray diffraction and report the phase transition into the spinel‐type phase at 47 GPa and 1800 K in a laser‐heated diamond anvil cell. The structure of spinel‐type BeP2 N4 was refined from pressure‐dependent in situ synchrotron powder X‐ray diffraction measurements down to ambient pressure, which proves spinel‐type BeP2 N4 a quenchable and metastable phase at ambient conditions. Its isothermal bulk modulus was determined to 325(8) GPa from equation of state, which indicates that spinel‐type BeP2 N4 is an ultraincompressible material. Abstract : Nitridspinell : Mittels einer laserbeheizten Diamantstempelzelle wurde BeP2 N4 bei 47 GPa und 1800 K vom Phenakit‐Typ in den Spinell‐Typ umgewandelt. Dessen Kristallstruktur wurde in situ mit druckabhängigen Synchrotron‐XRD‐Messungen untersucht und der isotherme Kompressionsmodul wurde auf >300 GPa bestimmt, was die Spinell‐Form von BeP2 N4 als ultra‐inkompressibles Material klassifiziert.